Gambaran Keterampilan Ibu Tentang Cara Memandikan Bayi Pada Ibu Postpartum Di PMB SR - Cintya Whinike; Suprapti Suprapti; Ita Yuliani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: one of the activities that create a bonding between mother and child is bathing the baby. But most mothers are afraid when doing it, this is because the baby's physical condition is still weak. Therefore, it is important for postpartum mothers to know how to bathe the baby correctly and safely. However, based on preliminary studies conducted at PMB SR, it was found that most postpartum mothers still use shamans or in-laws to bathe their babies. Objective: to determine the skills overview postpartum mothers in PMB SR. The benefits of research for the population in the research area are to increase the knowledge and skills of postpartum mothers about how to bathe babies properly and safely, so as to prevent hypothermia, infection, and infant death, and increase bonding attachment between mother and baby. Research design: this study uses a descriptive design with a cross sectional approach. the population of all postpartum mothers in PMB SR who met the inclusion criteria amounted to 30 people in the period 08 May - 08 June 2023 the measuring instrument in this study was the baby bathing skills checklist. Results: from the results of descriptive analysis obtained, respondents with skilled categories of 7 people (23%), and unskilled obtained 23 people (77%). Discussion: based on the results obtained, most postpartum mothers are not skilled in bathing their babies. It is expected that this study can be used as data to improve the skills of mothers by changing the method in the class of pregnant women from lectures to a combination of lectures and demonstrations.